Blessed Are the Peacemakers : Small Histories During World War II, Letter Writing, and Family History Methodology. - Rumsey, Suzanne Kesler, 1977- (: University of Alabama Press, 2021)
"An uncommon and intimate account of the lives of two conscientious objectors"--
Chapter 12. Daily Life at the State Hospital -- Chapter 13. Finances and More Conflicts -- Conclusion -- Notes -- Bibliography -- Index
Description based upon print version of record.
eBooks on EBSCOhost
Keywords: Kesler, Benjamin Elias, -- Jr., -- 1920-1981.; Kesler, Miriam Elizabeth, -- 1925-2013.; Civilian Public Service -- Biography; Dunkard Brethren -- Biography; Civilian Public Service; Dunkard Brethren; World War, 1939-1945 -- Conscientious objectors -- United States -- Biography; Conscientious objectors -- United States -- Biography; Pacifists -- United States -- Biography; Married people -- United States -- Correspondence; Letter writing -- United States; Genealogy -- Authorship; Guerre mondiale, 1939-1945 -- Objecteurs de conscience -- États-Unis -- Biographies; Objecteurs de conscience -- États-Unis -- Biographies; Pacifistes -- États-Unis -- Biographies; Couples mariés -- États-Unis -- Correspondance; Social Activists; BIOGRAPHY & AUTOBIOGRAPHY; World War II; Military; HISTORY; 20th Century; United States; Composition & Creative Writing; Letters; LITERARY COLLECTIONS; Conscientious objectors; Genealogy -- Authorship; Letter writing; Married people; Pacifists; United States; 1939-1945; e-books.; Biographies; Personal correspondence; Livres numériques.